The Catholic Context in Bonhoeffer's Lifetime - Dietrich, Donald J. (Studies in Christian-Jewish Relations, 2011)
Delivered during a panel discussion entitled "Bonhoeffer's Context: The Churches' Responses to Nazism" during the conference Dietrich Bonhoeffer for Our Times: Jewish and Christian Perspectives, cosponsored by the Center for Christian-Jewish Learning at Boston College, the United States Holocaust Memorial Museum, Hebrew College, and Andover-Newton Theological School, September 17, 2006. The essay discusses the lack of resistance by the Catholic Church in general and, with some exceptions, by Catholic theologians in particular.